Living with climate variability and change: lessons from Tanzania - Pauline, Noah Makula (My University, 2015)
There is sufficient evidence supporting that climate change and variability are pervasive realities that are strongly impacting on smallholder farmers in the Great Ruaha River sub-Basin of Tanzania. This PhD study examines smallholder farmers’ vulnerability, coping and adaptation strategies to climate change and variability (including non-climatic stresses), and investigates how such coping and adaptation may be constrained or enhanced given climate variability and change. Both quantitative and qualitative data collection methods were used when engaging with smallholder farmers and government officials. Primary data collection was undertaken in two phases, with phase one using participatory tools (e.g. focus group discussions, wealth ranking, community mapping and transect walk, and historical time lines). Data collected include climatic and non-climatic extreme events, farmers’ perceptions, coping and adaptation strategies. Phase two involved detailed individual interviews (questionnaire surveys) and key informant interviews (case studies), so as to obtain in-depth information on issues of interest. Secondary data were collected from existing statistical sources, literature surveys in archives, libraries and documentation centres, and from governmental agencies (e.g. TMA). Demographic, agricultural production and livestock statistics, and rainfall and temperature records were collected. Results from selected meteorological stations and farmers’ perceptions (74%) indicate that there has been an increase in average maximum temperatures, and both dry and wet years with varying magnitudes during the past four decades. Other climatic stresses include delayed onset and later cessation of the rain seasons. The agreement between farmers’ perceptions and rainfall trends provides good evidence that the climate has become increasingly variable in the GRRB during the past four decades. Achieving sustainable livelihoods is further compounded by non-climatic stresses such as access to markets and coordinating institutions. Results indicate that vulnerability is a complex phenomenon that entails two approaches (end-point and starting-point perspectives). The end-point perspective views vulnerability as the net projected climate change impacts after adaptation has taken place, whilst the starting-point perspective looks at both the current and future multiple stresses and places much emphasis in improving the adaptive capacity. In the study villages, such a nuanced picture highlighted areas for enhanced adaptation strategies. Farmers respond by using various strategies to deal with droughts, floods and other stresses when they occur. During droughts, they mostly use irrigation (canal, pumping and cans), or plant short-term maturing crops. During food shortages, farmers use strategies such as buying food, borrowing money, temporary migration, working in other people’s farms for cash, and reducing consumption. Moreover, the farmers’ choice of adaptation and coping strategies is influenced by factors such as location, access to resources, education levels and institutions. This calls for a whole system approach, which entails defining vulnerability of smallholder farmers to climatic and non-climatic stresses and thus designing appropriate response strategies. For example, mainstreaming adaptation to such stresses when considering development plans, projects, programmes and policies at all scales.
A Thesis Submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy May, 2015.
Keywords: Smallholder farmers.; Great Ruaha River sub-Basin.; Tanzania.; Stresses.; Impacts.; Vulnerability.; Coping.; Adaptation.; Climate change.; Climate variability.; Climatic changes.; Climatic changes--Social aspects.; Climatic changes--Environmental aspects--Tanzania.; Farmers--Tanzania.